PEMBUATAN DAN PENGUJIAN ALAT UNTUK MENENTUKAN KONDUKTIVITAS PLAT SENG, MULTIROOF DAN ASBES - Ersi Selparia; Maksi Ginting; Riad Syech (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The use of conductors and insulators as household supplies industrial materials is increasing now a days. In this study, it carried out the design and testing tools todetermine the conductivity of Zinc plate, multiroof and asbestos. The method is heat transfer conduction by using an electric circuit of source direct current (DC). The result shows the largest conductivity values contained in the Zinc plate is 0.482 W / m°C and the lowest value is multiroof conductivity of 0.132 W / m°C.